Lacrimal Gland Measurements in Patients with Graves’ Ophthalmopathy - Yuksel, MD, Elmas; Sukun, MD, Abdullah (International Journal of Innovative Research in Medical Science, 2022)
Purpose: Lacrimal gland sizes are increased in Graves' ophthalmopathy. Lacrimal gland herniation has been reported to be a simple radiological marker. This study aimed to investigate the relationship of lacrimal gland herniation (LGH) with lacrimal gland dimensions, proptosis, and hormonal parameters. Methods: Sixty-eight eyes of 34 patients with Graves' ophthalmopathy were evaluated. Lacrimal gland herniation, proptosis, the long and short axis of the lacrimal gland were measured in mm on the right and left sides. TSH, FT4, FT3, Anti-TPO and Anti-TG values of each patient were recorded. Multiple linear regression was applied to determine the factors affecting lacrimal gland herniation. Results: 21 female 13 male 34 patients were included in this study. The mean age of the patients was found to be 37.29±11.91 years The regression model for LGH was found to be statistically significant. (R2 right eye :0.57 R2 left eye 0.51 p<0.001). The predictive variables for LGH were short diameter of the lacrimal gland and proptosis. No statistical significance was found in other variables (p<0.05). The equation showing right LGH in millimeters was found as-5.268+ Lacrimal gland short-axis x 1.271 + Proptosis x 0.284. The equation showing left LGH in millimeters was found as-3.598+ lacrimal gland short-axis x 0.937 + Proptosis x 0.292. Conclusions: Lacrimal gland herniation is associated with lacrimal gland short diameter and proptosis. Our findings support that lacrimal gland herniation may be an important and useful radiological marker in Graves' ophthalmopathy.